Peranan Perempuan Dalam Meningkatkan Kewirausahaan Dalam Pembangunan - Anisa Binar Cahyani; Sulasi Imaniah; Puja Damaskha Rulita Sari; Ananda Hidayat; Dwi Taufiq Aziz; Heni Noviarita (Universitas Mitra Indonesia, 2021)
The purpose of this journal is to find out the role of women in increasing entrepreneurship in development. The data used is secondary data, where this journal takes data from sources such as books, articles, and readings. The method used is qualitative. Based on the results or discussion, women are one of the great strengths. Women's entrepreneurship is considered capable of changing social and economic values. Women have many important roles for the welfare of the family and the welfare of society. In addition to the main role of women as housewives who take care of and educate children, women also have an important role in building welfare in society. The empowerment of women in supporting MSMEs in Indonesia has enormous potential and must be optimized by the central and regional governments.